THE USE OF PICTURES AND SENTENCE COMPLETION DRILLS IN SPEAKING TEACHING-LEARNING ACTIVITY - Magdalena Br. Marpaung; Ismarini Hutabarat (JURNAL LITTERA: FAKULTAS SASTRA DARMA AGUNG, 2022)
Speaking is a very important skill in language proficiency. As a main skill to have in all languages, speaking is taught in various ways. Theoretically, pictures are a good media to be used to increase learners interest and sentence completion drills are good to make the teaching-learning activities to be fun. Based on the observation, in this teaching-learning activities, pictures are very good in enhance learners interest and focus while sentence completion drills are very good in turning the class to be fun and relax, sentence completion drills increase the interaction of teacher to learners and learners to learners. Moreover, sentence completion drills are very good to attract students starting either creating a conversation. The use of pictures and sentence completion drills are two very good combination in classroom in teaching-learning speaking.